Miguel de Unamuno's Quest for Faith A Kierkegaardian Understanding of Unamuno's Struggle to Believe. - Evans, Jan E. (Havertown : James Clarke & Co, 2014)
Miguel de Unamuno (1864-1936) was a extraordinary Spanish thinker, a philosopher, linguist, poet, novelist, short story writer, essayist, playwright, professor, university administrator, and Spanish public intellectual. He had great intellectual integrity and moral courage.Unamuno is not an easy philosopher to read. He loved paradoxes and even (at times) contradictions. Various interpreters have called him an atheist, a sceptic, a Protestant, a pantheist, a Catholic modernist, and a good Catholic. Passages can be found in his writings that can be taken to support all of these interpretations.
Front Cover; Title Page; Copyright information; Contents; Foreword; Acknowledgments; Abbreviations; 1. Introduction; 2. Miguel de Unamuno's Life and Spiritual Formation; 3. Truth Must Be Lived; 4. Unamuno's Passion for Immortality; 5. Unamuno, Kierkegaard, and Pascal on the Role of Doubt in Faith; 6. The Unhealed Wound; 7. Unamuno's Faith and Kierkegaard's Religiousness A; 8. Conclusion; Bibliography; Back Cover
Description based upon print version of record.
Keywords: Unamuno, Miguel de, -- 1864-1936 -- Criticism and interpretation; Unamuno, Miguel de, -- 1864-1936 -- Religion; Kierkegaard, Søren, -- 1813-1855.; Spanish literature -- History and criticism; Religion in literature; PHILOSOPHY / History & Surveys / Modern; Electronic books